Pomegranate Fruit Growth and Skin Characteristics in Hot and Dry Climate - Joshi, Mukul; Schmilovitch, Ze’ev; Ginzberg, Idit (Frontiers in Plant Science, 2021)
Pomegranate (Punica granatum L.) fruit is well known for its health-beneficial metabolites. The pomegranate peel consists of an inner thick spongy white tissue, and an outer smooth skin layer that accumulates anthocyanins in red cultivars when ripe. The skin is made up of epidermis cells covered by a cuticle, the latter being the first target of cracking and russeting. The present study focuses on the effect of Israel's hot and dry climate on pomegranate growth, to elucidate the derived effects on fruit skin characteristics and its putative resistance to the building pressure from fruit expansion. Experiments were conducted for four years, in four orchards located in different regions of the country, each with a different typical microclimate. Fruit-growth parameters were followed using remote-sensing tools, microscopic study and mineral analysis of the skin, followed by determination of the peel's elastic modulus. Fruit expanded in two phases: a short rapid phase followed by a gradual phase with a sigmoidal growth-rate pattern. Extreme hot and dry climate during the period of maximal growth rate was associated with restricted growth and a high proportion of small-size fruit. Anatomical study indicated that the skin of mature pomegranate fruit is made up of epidermal cells that are relatively flat and spaced apart, and is expected to be less durable against internal pressure. In contrast, skin of early immature fruit has two layers of dense and rounded epidermis, and is expected to be more resistant to cracking. Tensile strength studies confirmed this trend—skin of mature fruit had a lower elastic modulus than young fruit. However, restrained growth due to extreme environmental cues may result in better resistance of the mature pomegranate fruit to cracking, resulting in better skin quality and appearance, albeit small fruits. On the other hand, temperate climate at the beginning of the growth period, which allows high growth rate and high daily shrinkage, leads to pomegranate skin disorders.